Membangun ketahanan pangan terhadap peternakan sapi bali Seluma selatan kelurahaan rimbo kedui - Melinda, Tri Febrina; saputra, Arzil azizah; Pranata, Fheroansyah Ade; Abi, Yudi Irawan; Irwanto, Tito (Jurnal Dehasen Mengabdi, 2023)
Building food security for Bali cattle farming is very important for the sustainability of their livestock, but many breeders do not understand this, therefore I chose the South Seluma area of Rimbu Tavern Village to be my place of service because there are cattle farms that experience this problem, and breeders besides their lack of understanding regarding food development they also have difficulty when the dry season arrives to feed their cows and finally sell, and I finally did PKM there to provide knowledge and creative innovation for cattle food when the dry season arrives by means of counseling to cattle breeders.